THE BRAZILIAN SCENARIO OF TRANSGENIC FOOD - Rodrigues, Tailine da Silva; Vieira, Vanessa Amaro (Revista Interface Tecnológica, 2023)
Genetically modified foods have always been the subject of discussions around the world. Such questions have always been based on the benefits and harms of these foods in both human and animal health, in addition to the concern of the socioeconomic and environmental impacts that they can cause over time. Within this context, the aim of this study is to address transgenic foods, covering their history, scientific development, also highlighting their negative and positive impacts on human health and the environment. The methodology used was a literature review, with consultations in articles arranged in Google Scholar and SciELO. The results show that transgenic foods do not bring harm to human health, on the contrary, the absence of addition of pesticides can bring positive results both for human health and to reduce environmental impacts.
Keywords: Food; Health; Transgenic